Characteristics and Outcomes of Heart Failure Patients from a Middle-Income Country: The RECOLFACA Registry - Juan Esteban Gomez-Mesa; Clara Saldarriaga; Luis Eduardo Echeverría; Alex Rivera-Toquica; Paula Luna; Sebastián Campbell; Lisbeth Natalia Morales; Juan David López Ponce de León; Andrés Felipe Buitrago; Erika Martínez; Jorge Alberto Sandoval; Alexis Llamas; et al. (Ubiquity Press, 2022)
Background: There is a lack of epidemiological data around heart failure (HF) in Latin America; the potential impact description of this disease in middle-income countries is relevant. Objective: This study aimed to describe the characteristics and healthcare resource utilization patterns of HF patients at baseline and six-month follow-up. Methods: This retrospective observational study used data from the RECOLFACA ('Registro Colombiano de Falla Cardíaca') registry, which includes data obtained from the examination of clinical records from 2,528 patients in 60 Colombian healthcare institutions. Baseline and six-month follow-up data were evaluated from patients with previous hospital admissions due to HF during the 12 months prior to enrollment. Results: This study analyzed 2,045 patients (42.8% female) with a mean age of 67.71 ± 13.64 years. The most common etiologies were ischemic (44.4%) and hypertensive heart disease (38.5%). At baseline, 53.4% of patients were classified with NYHA class II, and 73.6% had a reduced left ventricle ejection fraction (LVEF). A year prior to entering the registry, patients were hospitalized an average of 1.4 ± 1.1 times due to HF. Prescription of evidence-based treatment at baseline included sacubitril/valsartan (10%), ACEI (33%), ARB (41%), beta-blocker (79%), diuretics (68%), and MRA (56%). The average quality of life score measured using the EQ-5D-3L questionnaire was 78.7 ± 20.8 at baseline and 82.3 ± 20.1 at the six-month follow-up. The mortality rate was 6.7%. Conclusions: The use of information from the RECOLFACA registry allowed characterization as well as analyses of healthcare resource utilization of patients with heart failure in Colombia. The results of this study show that multiple evidence-based treatments for HF are being widely used in Colombia, but there seems to be room for improvement regarding some interventions for the treatment of patients with HF.